Penggunaan Aplikasi Berbasis Smartphone tentang Pengayaan Materi Kebugaran Jasmani di SMP Se-Kecamatan Kartasura - Saputra, Ardhian Bachtiar Panca; Putra Aji, Ranu Baskora (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of this study is to describe the use of smartphone-based applications for learning physical fitness in grades 7–9. The research was carried out by junior high schools in Kartasura District, Sukoharjo Regency, Central Java. The data collection technique for this research used a questionnaire method with descriptive data analysis techniques using IBM Statistics 21. The results of this study indicate that the majority of respondents chose TKJI and SAQ Training Grade 8. Teacher knowledge on 7 physical fitness applications in the "Good" category was 79%, teacher interest in 7 physical fitness applications was in the "Good" category 77%, teacher perceptions on 7 applications physical fitness in the "Good" category 80%. The conclusion in this study is that the teacher previously did not know about the application because of a lack of socialization. After reading the application review book, the respondents were interested in choosing the one with the most choices in the SAQ Training application, with seven enthusiasts. However, if the application is used to learn physical fitness material, it is less effective because of the lack of socialization associated with its use and because not all students have smartphones.